Human governance approach in building high performing learners / Wahidah Mansor and Bibi Norashiqin Sheikh Rahimullah - Mansor, Wahidah; Sheikh Rahimullah, Bibi Norashiqin (UiTM Press, 2020)
Academic dishonesty and unethical behaviours such as cheating and plagiarism are obstacles to innovative and creative thinking and mastering the course materials. Recognition of human values and principles from the internal drivers can drive and motivate individuals to excel beyond expectation. Various programmes have been executed to encourage ethical student behaviour. However, the programmes are not an integral part of the course. This paper describes the method used to build consciousness at a deeper level in one of the Electronic Engineering courses for the purpose of producing high performing learners with good values. A strategy was developed where a mechanism was used to make the learners realize the correct way of sharing knowledge and the wrongdoings in academic that may become their habit and usual practice. Being human was stressed in the first lecture with the realization of the purpose of life and discussion on the code of conduct as a learner and effect of academic dishonesty on society.